Peran Promosi, Kualitas Website, dan Kepercayaan dalam Meningkatkan Kepuasan Pelanggan E-Commerce Blibli - Ramadhan, Ibnu Cahyo; Supriyadi, Muhammad Edy; Aldila Kurnia Dian Permata Sari (Journal of Trends Economics and Accounting Research, 2025)
The purpose of this study is to analyze the effect of Promotion, Website Quality, and Trust on Blibli E-commerce customer satisfaction. The analysis method in this study uses quantitative primary data, the test stages carried out are: validity test, reliability, normality, multiple linear regression, coefficient of determination, F test, and t test. The data used in this study used a questionnaire instrument, and valid data that had been collected were 100 respondents. The sampling method in this study was non-probability sampling with purposive sampling technique. The test tools used included classical assumption test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, coefficient of determination (R2), hypothesis test including statistical test (F test) and partial test (t test) using SPSS 26 software. The results of this study indicate that the promotion variable has a partial effect on customer satisfaction, the website quality variable does not have a partial effect on customer satisfaction, and the trust variable has a partial effect on customer satisfaction, the most dominant variable on customer satisfaction is the promotion variable. Keywords: Promotion, Website quality, promotion, customer satisfaction.